New Innovation Trends of the Western World - Paduchak, B.M. (Science and Innovation, 2024)
New forms of scientific cooperation have been described. The global trends in the general principles of scientific research have been defined. The main problems related to funding of fundamental science have been outlined. The necessity of implementing the effective forms of public private partnership (PPP) in innovation has been substantiated. New level of innovation culture should be based on the principle of cooperation of all the entities engaged in creation and commercialization of innovations.